Knowledge of Risk Factors of Cancer Among Nepali Immigrants in Japan - Poudel, K; Noguchi, M; Sumi, N (KnE Life Sciences, 2019)
Cancer accounts for 30% mortality in Japan. Increasing the basic knowledge on Cancer is vital to decrease the burden of cancer treatment and medical expenses. Since Nepal is the largest South Asian community in Japan, it is necessary to assess their awareness of Cancer. The purpose of this study was to identify cancer awareness among Nepali immigrants in Japan. A descriptive, cross-sectional study was conducted Hokkaido prefecture, Japan. A snowball sample of 100 Nepali immigrants aged 20-45 years participated in this study. SPSS V.22.0 was used for regression and descriptive analysis. Most immigrants (67%) were in between 31 and 45 years old and male (73%). Almost 21% did not have health insurance in Japan. The smoking rate was low (12%) while the alcohol rate was high (65%) among immigrants. Internet was reported to be the most common source of information. A total of 87% of immigrants showed a strong need for cancer education. The total range of score was 0-9. Female, university-level education, family history of chronic illness, and immigrants with the daily habit of healthy diet had better knowledge about risk factors of Cancer. Multiple regressions showed education level, length of stay, and healthy diet habit as a significant factor for knowledge about cancer (R2 = 0.34, p<0.01). There was limited knowledge on risk factors of cancer among Nepali immigrants. This study showed a strong need for awareness about cancer and screening tests to ameliorate the increased risk of cancer. Keywords: Risk factors, Cancer, Immigrants, Knowledge, Nepali